Ceftolozane/Tazobactam Dosing Requirements Against Bacteremia - Jesus Ruiz; Alejandra Ferrada; Miguel Salavert; Mónica Gordon; Esther Villarreal; Álvaro Castellanos-Ortega; Paula Ramirez (SAGE Publishing, 2020)
Objectives: To assess the probability of reaching adequate pharmacokinetic/pharmacodynamics values for ceftolozane/tazobactam at different doses and degrees of renal functions in patients with Pseudomonas aeruginosa bacteremia. Methods: Six dosing regimens were evaluated: 0.5/0.25 g, 1/0.5 g, and 2/1 g every 8 hours given as 1 hour or 3 hours infusions. Pharmacokinetic data were obtained from the literature. Susceptibility data to ceftolozane were collected from patients with P aeruginosa infection treated with ceftolozane-tazobactam. Probability of reaching a fraction of time (fT) >40% minimum inhibitory concentration (MIC) and fT >100%MIC value for ceftolozane at 3 different renal clearance values was evaluated. For tazobactam, the probability of reaching an fT >40% and >70% for 3 limit values was calculated. Results: Thirty-seven strains were included. For ceftolozane, the probability of reaching a fT >40%MIC was greater than 90% for any degree of renal function. The probability of reaching a fT >100%MIC for 1 g dose infused over 1 hour and 3 hours was 82.2% and 86.4% for a creatinine clearance (ClCr) >90 mL/min. Using a 2 g dose, the probability was greater than 90% for both infusions rates. For tazobactam, the probability of reaching a value of fT >50% of the limit concentrations was greater than 90% for a ClCr of 70 mL/min. In the case of a ClCr >90 mL/min and limit concentration values ≥ 0.25 mg/mL, only extended infusions showed a probability >90%. Conclusions and Relevance: The standard doses of ceftolozane/tazobactam achieve an adequate fT >40%MIC value. However, doses of 2 g in extended infusion is necessary to reach a value of fT >100%MIC, especially in patients with an increased renal clearance and high levels of beta-lactamases expression.